Microeconomic Analysis of Time-use Data. Did we reach the promised land? - Anders Klevmarken (Uppsala University, Department of Economics, 1998)
This paper surveys the last decade of micro-economic research using time-use data. Focusing on the household production model, time-use as an investment activity, and the distribution of extended income, issues of data collection, measurement errors, model specification and estimation as well as substantive results are reviewed and discussed. Although time-use data have specific characteristics which need be considered in analysis there is more to learn from these data and in particular if present short-comings are dealt with in future data collection.
urn:nbn:se:uu:diva-2419
Keywords: C81; D13; J22; 330; time-use; household production; labor supply; auxiliary information